Preservice teachers’ teaching internship affects professional identity: Self-efficacy and learning engagement as mediators - Cai, Zhiling; Zhu, Jinxing; Tian, Saiqi (Frontiers in Psychology, 2022)
Preservice teachers’ professional identity is a critical factor in their motivation, effectiveness, and retention. Teaching internship can promote the transformation of professional identity and self-efficacy of preservice teachers. The internship environment also enhances students’ increasing level of learning engagement. Although much research has shown strong relationship between preservice teachers’ teaching internship and professional identity, less is known about how self-efficacy and learning engagement mediated those variables. The purpose of this study is to investigate the roles that self-efficacy and learning engagement play in the relationship between preservice teachers’ professional identities and their teaching internship experiences. The study involved 309 preservice teachers in total, and the variables were measured using questionnaires. For the data analysis, we used structural equation modeling. The study’s findings are as follows. (a) Teaching internship, professional identity, self-efficacy, and learning engagement were all significantly correlated with one another. (b) Both self-efficacy and learning engagement partially mediated the relationship between teaching internship and professional identity in a parallel manner. (c) Self-efficacy and learning engagement also sequentially mediated the relationship between teaching internship and professional identity.